Cultural Consumption and Citayam Fashion Week: Study of Meaning of TikTok Content - Silfia, Imamatul (UI Scholars Hub, 2023)
This thesis examines the consumption practices of fashion culture and the meaning of TikTok content in the Citayam Fashion Week phenomenon. Scholars have studied cultural consumption as a factor that creates social class hierarchies based on cultural capital or tastes, including the consumption of fashion culture. Hierarchy in the practice of cultural consumption of fashion places the working class in an artistically inferior position compared to the elite class. The fashion tastes of the working class are considered to be economically limited and they primarily imitate the tastes of the dominant class. This assumption considers the cultural appropriation of working-class fashion as foreign and subordinate. Following this assumption, this thesis studies the trend of the Citayam Fashion Week phenomenon which is popular through social media TikTok. It researches Citayam Fashion Week participants who come from the working class. For this reason, this study analyzes the consumption practices of Citayam Fashion Week participants' fashion culture and how they interpret the trend of TikTok content in order to understand the phenomenon from the participants' side. This study shows that Citayam Fashion Week participants consume fashion culture in distinctive ways, namely by exploring fashion, pragmatic consumption, and passive consumption. Meanwhile, participants also have specific interpretations of TikTok content. From the findings, the study concluded that there is a social hierarchy in the Citayam Fashion Week phenomenon through the practice of consuming fashion culture and TikTok content trends. The fashion appropriation of Citayam Fashion Week participants is treated as something foreign and their representation and identity are determined by the dominant group. These findings show that consumption of fashion culture and TikTok content trends regarding Citayam Fashion Week perpetuate control of the class and economic positions by the dominant group.